NEWTON-2 Cisternal (Nimodipine Microparticles to Enhance Recovery While Reducing Toxicity After Subarachnoid Hemorrhage): A Phase 2, Multicenter, Randomized, Open-Label Safety Study of Intracisternal EG-1962 in Aneurysmal Subarachnoid Hemorrhage. Issue 1 (28th September 2020) - Macdonald, R Loch; Hänggi, Daniel; Ko, Nerissa U; Darsaut, Tim E; Carlson, Andrew P; Wong, George K; Etminan, Nima; Mayer, Stephan A; Aldrich, E Francois; Diringer, Michael N; Ng, David; Strange, Poul; et al.
ABSTRACT: BACKGROUND: A sustained release microparticle formulation of nimodipine (EG-1962) was developed for treatment of patients with aneurysmal subarachnoid hemorrhage (aSAH). OBJECTIVE: To assess safety, tolerability, and pharmacokinetics of intracisternal EG-1962 in an open-label, randomized, phase 2 study of up to 12 subjects. METHODS: Subjects were World Federation of Neurological Surgeons grades 1 to 2, modified Fisher grades 2 to 4, and underwent aneurysm clipping within 48 h of aSAH. EG-1962, containing 600 mg nimodipine, was administered into the basal cisterns. Outcome on the extended Glasgow Outcome Scale (eGOS), pharmacokinetics, delayed cerebral ischemia and infarction, rescue therapy, and safety were evaluated. RESULTS: The study was halted when a phase 3 study of intraventricular EG-1962 stopped because that study was unlikely to meet its primary endpoint. Six subjects were randomized (5 EG-1962 and 1 oral nimodipine). After 90-d follow-up, favorable outcome on the eGOS occurred in 1 of 5 EG-1962 and in the single oral nimodipine patient. Four EG-1962 and the oral nimodipine subject had angiographic vasospasm. One EG-1962 subject had delayed cerebral ischemia, and all subjects with angiographic vasospasm received rescue therapy except 1 EG-1962 patient. One subject treated with EG-1962 developed right internal carotid and middle cerebral artery narrowing 5 mo after placement of EG-1962, leading to occlusion and cerebral infarction. Pharmacokinetics showed similar plasma concentrations of nimodipine in both groups. CONCLUSION: Angiographic vasospasm and unfavorable clinical outcome still occurred after placement of EG-1962. Internal carotid artery narrowing and occlusion after placement of EG-1962 in the basal cisterns has not been reported.